Maxillary Rhinosinusitis Profil In General Hospital Of Haji Surabaya On January-December 2017 - Indra Setiawan (Saintika Medika, 2021)
Chronic rhinosinusitis in various countries in the world and Indonesia shows an increase from time to time. At General Hospital of Haji Surabaya, the prevalence of chronic rhinosinusitis has increased from 10.13% in 2016 to 10.26% in 2017. Various factors are thought to cause chronic rhinosinusitis. Chronic rhinosinusitis can interfere with the quality of life and lead to serious complications if left untreated. To determine the profile of chronic rhinosinusitis in General Hospital of Haji Surabaya for January-December 2017 Period. Analytic observational with cross-sectional study approach. Used the total sampling method. Based on patients diagnosed with chronic rhinosinusitis with complete medical record data. The sample in this study were 132 patients. Most chronic rhinosinusitis patients were aged 36-45 years as many as 26 patients (19.69%) and the least number of patients was more than 65 years old as many as 6 patients, women (67.40%) and 43 patients in men (32, 60%). Symptoms of nasal congestion in 79 patients (59.84%), cough as many as 25 patients (18.93%), septal deviation as many as 51 patients (38.63%) and at least 4 patients (3.03%) of nasal polyps. Most rhinosinusitis patients in this study were aged 36-45 years, women with symptoms of nasal congestion and septal deviation as the most comorbidities.